Identification of an Important Orphan Histidine Kinase for the Initiation of Sporulation and Enterotoxin Production by Clostridium perfringens Type F Strain SM101 - John C. Freedman; Jihong Li; Eric Mi; Bruce A. McClane (mBio, 2019)
ABSTRACT Clostridium perfringens type F strains cause a common human foodborne illness and many cases of nonfoodborne human gastrointestinal diseases. Sporulation plays two critical roles during type F enteric disease. First, it produces broadly resistant spores that facilitate type F strain survival in the food and nosocomial environments. Second, production of C. perfringens enterotoxin (CPE), the toxin responsible for causing the enteric symptoms of type F diseases, is restricted to cells in the process of sporulation. While later steps in the regulation of C. perfringens sporulation have been discerned, the process leading to phosphorylation of Spo0A, the master early regulator of sporulation and consequent CPE production, has remained unknown. Using an insertional mutagenesis approach, the current study identified the orphan histidine kinase CPR0195 as an important factor regulating C. perfringens sporulation and CPE production. Specifically, a CPR0195 null mutant of type F strain SM101 made 103-fold fewer spores than its wild-type parent and produced no detectable CPE. In contrast, a null mutant of another putative C. perfringens orphan histidine kinase (CPR1055) did not significantly affect sporulation or CPE production. Studies using a spoIIA operon promoter-driven reporter plasmid indicated that CPR0195 functions early during sporulation, i.e., prior to production of sporulation-associated sigma factors. Furthermore, in vitro studies showed that the CPR0195 kinase domain can autophosphorylate and phosphorylate Spo0A. These results support the idea of CPR0195 as an important kinase that initiates C. perfringens sporulation by directly phosphorylating Spo0A. This kinase could represent a novel therapeutic target to block C. perfringens sporulation and CPE production during type F disease. IMPORTANCE Clostridium perfringens type F enteric diseases, which include a very common form of food poisoning and many cases of antibiotic-associated diarrhea, develop when type F strains sporulate and produce C. perfringens enterotoxin (CPE) in the intestines. Spores are also important for transmission of type F disease. Despite the importance of sporulation for type F disease and the evidence that C. perfringens sporulation begins with phosphorylation of the Spo0A transcriptional regulator, the kinase phosphorylating Spo0A to initiate sporulation and CPE production had not been ascertained. In response, the current report now provides identification of an orphan histidine kinase named CPR0195 that can directly phosphorylate Spo0A. Results using a CPR0195 null mutant indicate that this kinase is very important for initiating C. perfringens sporulation and CPE production. Therefore, the CPR0195 kinase represents a potential target to block type F disease by interfering with intestinal C. perfringens sporulation and CPE production.